2013
DOI: 10.1177/1098612x13515461
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of expiratory flow pattern in feline lower airway disease

Abstract: Feline lower airway disease (FLAD) is a chronic respiratory disease of which there is a lack of information on functional assessment in current veterinary medicine. The purposes of this study were to investigate expiratory pattern and evaluate the diagnostic utility of functional parameters in cats with FLAD. Thirty-three client-owned cats (23 FLAD cats and 10 control cats) were studied. Under quiet tidal breathing, pseudo-tidal breathing flow-volume loop (pTBFVL) was obtained from a barometric whole body plet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 28 publications
1
33
3
Order By: Relevance
“…The pressure signal of the system was calibrated before each measurement by dynamic injection of 50 mL air into the chamber. Under quiet tidal breathing, the pseudotidal breathing flow‐volume loop (pTBFVL) and conventionally‐used BWBP parameters were acquired at the same time as described elsewhere . Artifactual waveforms caused by sniffing, vocalization, and body movements were automatically excluded and manually eliminated by the rejection setting of the commercial software (BioSystem XA 2.11.0 software) and simultaneous visual inspection, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pressure signal of the system was calibrated before each measurement by dynamic injection of 50 mL air into the chamber. Under quiet tidal breathing, the pseudotidal breathing flow‐volume loop (pTBFVL) and conventionally‐used BWBP parameters were acquired at the same time as described elsewhere . Artifactual waveforms caused by sniffing, vocalization, and body movements were automatically excluded and manually eliminated by the rejection setting of the commercial software (BioSystem XA 2.11.0 software) and simultaneous visual inspection, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although decreased airway responsiveness after treatment with steroids or bronchodilators could be evaluated by bronchoprovocation testing in experimental cats, bronchospasm at presentation prohibits further provocative stimulation and limits the ability to compare the provocative index before and after treatment in client‐owned cats. Aside from conventionally measured BWBP parameters and airway responsiveness testing, breathing pattern depicted by pseudoflow and pseudovolume may indirectly estimate respiratory mechanics during tidal breathing . The occurrence of small airway obstruction in cats with FLAD can result in substantial airflow limitation in the mid‐ to late‐expiratory phase, and a peak to midexpiratory flow ratio >1.51 identifies this obstructive pattern during tidal breathing .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-body barometric plethysmography (WBBP) is a non-invasive and objective technique to measure respiratory function while the animal is fully conscious and minimally restrained [1723]. The animal rests in the WBBP chamber and respiration causes barometric pressure oscillations proportional to tidal volume.…”
Section: Introductionmentioning
confidence: 99%
“…Whole‐body barometric plethysmography (WBBP) is a non‐invasive technique of measuring respiratory function that has been validated and utilized in unrestrained unsedated experimental mice to characterize respiratory patterns during sleep and wakefulness . This technique has also been used in experimental and clinical studies using dogs and cats for pharmacological studies and respiratory disorders . Our previous study on French bulldogs showed that respiratory airflow characteristics obtained from WBBP are distinguishable between BOAS‐affected and clinically healthy French bulldogs .…”
mentioning
confidence: 99%